2008
DOI: 10.1111/j.1745-7262.2008.00248.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pregnancies and livebirths achieved by intracytoplasmic injection of round headed acrosomeless spermatozoa with and without oocyte activation in familial globozoospermia: case report

Abstract: We report the successful outcome of intracytoplasmic sperm injection (ICSI) treatment in two siblings with familial globozoospermia. After controlled ovarian hyperstimulation and oocyte pick-up, retrieved oocytes were mechanically activated before ICSI and a fertilization rate of 33.3% was achieved in the first case. The second couple underwent ICSI without oocyte activation and a 9.1% fertilization rate was obtained. The transfer of two grade I embryos in the first couple and one grade I embryo in the second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 16 publications
0
41
0
Order By: Relevance
“…The presence of consanguineous marriages in families affected with globozoospermia and reports of two or more sibs in several families suggested a genetic contribution to globozoospermia in humans with an autosomal recessive mode of inheritance [6,[35][36][37][38][39][40]. Three genes segregating on an autosomal recessive mode have now been identified to be associated with globozoospermia in humans.…”
Section: Molecular Genetic Studiesmentioning
confidence: 99%
“…The presence of consanguineous marriages in families affected with globozoospermia and reports of two or more sibs in several families suggested a genetic contribution to globozoospermia in humans with an autosomal recessive mode of inheritance [6,[35][36][37][38][39][40]. Three genes segregating on an autosomal recessive mode have now been identified to be associated with globozoospermia in humans.…”
Section: Molecular Genetic Studiesmentioning
confidence: 99%
“…In total globozoospermia, a reduced ability to fertilize is described in about one-half of the cases reported, for which oocyte activation is applied in various reports (5)(6)(7)(8)(9)(10)(11)16). Because a previous study from our group (1) demonstrated an increased occurrence of structural abnormalities in ''normal'' oval spermatozoa derived from PG men, we anticipated that these ''normal cells'' that are picked for ICSI could have the impaired ability to fertilize in common with total globozoospermia.…”
Section: Discussionmentioning
confidence: 99%
“…The poor fertilization rates with ICSI may be due to deficient oocyte activation by these spermatozoa (4). Oocyte activation with calcium ionophores or electric activation has been applied in some studies and resulted in better fertilization rates in most cases (3,(5)(6)(7)(8)(9)(10)(11). To our knowledge, no augmented risk on congenital abnormalities has been reported in such pregnancies.…”
mentioning
confidence: 99%
“…Various methods of AOA, including the use of a calcium ionophore and electrical and mechanical stimuli, have been reported to be effective for fertilisation in men with globozoospermia. 3,4 Strontium treatment, which is proven to induce calcium oscillations in mice, was found to be an effective method for AOA in cases of low or absent fertilisation after ICSI. [5][6][7] Whether strontium is effective at improving fertilisation by globozoospermic sperm has not been reported.…”
mentioning
confidence: 99%
“…Assessment of the acrosome with fluorescent Pisum sativum agglutinin staining of the human spermatozoa was also conducted 9 ( Figure 1). Ultrastructural characteristics of the round-headed sperm were evaluated using a scanning electron microscope (JEOL Technics Ltd, Akishima-Shi, Tokyo, Japan) 3 (Figure 1). Spherical heads without acrosomes are shown.…”
mentioning
confidence: 99%